1979
DOI: 10.1136/jech.33.4.292
|View full text |Cite
|
Sign up to set email alerts
|

Community diagnosis of physical growth of infants based on monitoring in a routine preventive service.

Abstract: SUMMARYThe physical growth pattern of infants aged from one month to two years was studied in a lower middle class community in Jerusalem. Weight and length were measured at one month and at three, six, 12, and 24 months. In each age and sex group there were at least 200 children. At one month and 24 months the percentage of children below the 10th percentile for weight and also for length was higher than expected, although severely impaired linear growth was observed in only 0 5% of males and 1 3% of females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1982
1982
1993
1993

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…Birth weight is correlated with growth status during childhood. Palti et al (1979) found a n association between birth weight and growth in the two first years of life among children living in the same area as our study population. Similar findings among children through 5 years of age and 7 years of age (Garn, 1985) were also reported, with low birth weight babies tending to remain lighter and shorter than heavier babies.…”
Section: Discussionmentioning
confidence: 61%
“…Birth weight is correlated with growth status during childhood. Palti et al (1979) found a n association between birth weight and growth in the two first years of life among children living in the same area as our study population. Similar findings among children through 5 years of age and 7 years of age (Garn, 1985) were also reported, with low birth weight babies tending to remain lighter and shorter than heavier babies.…”
Section: Discussionmentioning
confidence: 61%
“…Por outro lado, as médias de peso e altura alcançadas pelo conjunto das crianças de uma determinada região indicariam fidedignamente as condições gerais de saúde e nutrição ali vigentes 3 . Demonstrações destes reconhecimentos podem ser vistas na incorporação da vigilância do crescimento aos programas de controle da saúde infantil 21,22 e na utilização de inquéritos antropométricos para monítorização do desenvolvimento social de países 16 .…”
Section: -Introduçãounclassified